1999
DOI: 10.1046/j.1365-2249.1999.00935.x
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD40 in the serum of healthy donors, patients with chronic renal failure, haemodialysis and chronic ambulatory peritoneal dialysis (CAPD) patients

Abstract: SUMMARYCD40 and its ligand CD40L are key players in T cell-B cell interaction and T cell-antigen-presenting cell (APC) interaction. Inhibition of CD40-CD40L interaction leads to severe humoral and cellular immunodeficiency. In this study we examined the presence of soluble CD40 (sCD40) in the serum of haemodialysis (HD) patients, CAPD patients, chronic renal failure (CRF) patients and healthy donors in order to evaluate the possible involvement of CD40 in uraemic immunodeficiency. Soluble CD40 was detected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 48 publications
3
20
0
2
Order By: Relevance
“…Several studies had demonstrated that patients with unstable angina, hypercholesterolaemia and diabetes have more elevated plasma levels of sCD40L than healthy subjects 19–24 . In agreement with one previous study, 25 in our study the plasma sCD40L concentration was increased in end‐stage renal disease (ESRD) patients on HD. More importantly, we also showed that HD patients with CHD are characterized by markedly raised plasma levels of sCD40L compared to normal controls and those HD patients without CHD.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies had demonstrated that patients with unstable angina, hypercholesterolaemia and diabetes have more elevated plasma levels of sCD40L than healthy subjects 19–24 . In agreement with one previous study, 25 in our study the plasma sCD40L concentration was increased in end‐stage renal disease (ESRD) patients on HD. More importantly, we also showed that HD patients with CHD are characterized by markedly raised plasma levels of sCD40L compared to normal controls and those HD patients without CHD.…”
Section: Discussionsupporting
confidence: 92%
“…In this context, it is conspicuous that the blood concentrations of sCD154 in seemingly asymptomatic patients with ESRD-regardless of the outcome-are higher than reported in recent studies in patients without ESRD even with acute coronary syndromes (13)(14)(15)20,21). This is in accordance with the results of a study in renal patients published by Schwabe et al (22).…”
Section: Discussionsupporting
confidence: 88%
“…The magnitude of this increase paralleled the flow cytometry results on the induction of CD40. Interestingly, it has been reported that patients with end-stage renal diseases have increased plasma levels of soluble CD40 [56,57]. The origin of this increase was linked to chronic renal failure but our study suggest that, at least in SLE, mesangial cell production of soluble CD40 could be a contributing factor.…”
Section: Discussionmentioning
confidence: 46%